Implementation of a Western-based multiliteracies pedagogy in Malaysia: a socio-cultural perspective - Fariza Puteh-Behak,; Ramiaida Darmi,; Yuslina Mohamed, (Penerbit UKM, 2015)
This paper discusses arising issues when a Western pedagogy in a Malaysian context is implemented. In finding a suitable pedagogy to address issues of low employability among Malaysian university graduates, academia prefers to implement a learning pedagogy such as multiliteracies approach from Western countries. However this practice is creating issues of adaptability among Malaysian students. Therefore this study investigates the implementation of the Multiliteracies pedagogy, a Western teaching approach; in a Malaysian university classroom that taught English as a Second Language (ESL). The method of the study was grounded to the philosophy of a participatory action research and data was collected through classroom observation, informal conversations and classroom artefacts. 30 Bakti Polytechnic students‟ experiences using the multiliteracies approach in learning ESL was the focus of this study. Due to the importance of reflection and action in a participatory action research, data was analysed through a Critical Reflective Analysis Steps, which included the process of observing and noting personal reflections, confronting and thinking, and taking action. The findings suggest that students had issues with working in teams, completing critical analysis and participating actively in classroom discussions. The study proposes a framework to guide the implementation of a Western-based pedagogy in a Malaysian context. Indeed, the practice requires deep deliberation of the students‟ socio-cultural practices and cultures of learning to ensure that optimum result could be achieved from the introduction of the new pedagogy.